2020
DOI: 10.21470/1678-9741-2019-0334
|View full text |Cite
|
Sign up to set email alerts
|

Sufentanil Reduces Emergence Delirium in Children Undergoing Transthoracic Device Closure of VSD After Sevoflurane-Based Cardiac Anesthesia

Abstract: Objective The aim of this study was to evaluate whether sufentanil can reduce emergence delirium in children undergoing transthoracic device closure of ventricular septal defect (VSD) after sevoflurane-based cardiac anesthesia. Methods From February 2019 to May 2019, 68 children who underwent transthoracic device closure of VSD at our center were retrospectively analyzed. All patients were divided into two groups: 36 patients in group S, who were given sufentanil and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The incidence of PCA-related adverse events, especially PONV in sufentanil 5 μg/kg, were lower than that in the tramadol-containing regimen (ST group), which is in agreement with the study of Pang et al, 13 who found that PCA with additional tramadol provided effective analgesia following major orthopedic surgery, but there was a high incidence of nausea and vomiting. Our study is also consistent with Stassinos et al, 14 who confirmed frequent vomiting in tramadol-treated pediatric patients.…”
Section: Pca-related Adverse Eventssupporting
confidence: 90%
“…The incidence of PCA-related adverse events, especially PONV in sufentanil 5 μg/kg, were lower than that in the tramadol-containing regimen (ST group), which is in agreement with the study of Pang et al, 13 who found that PCA with additional tramadol provided effective analgesia following major orthopedic surgery, but there was a high incidence of nausea and vomiting. Our study is also consistent with Stassinos et al, 14 who confirmed frequent vomiting in tramadol-treated pediatric patients.…”
Section: Pca-related Adverse Eventssupporting
confidence: 90%
“…Additionally, Sufentanil (26,716) has a higher therapeutic index than fentanyl (277) and morphine (71) according to preclinical studies, and it exhibits high bioavailability ( Helmers et al, 1989 ; Mather, 1995 ). Hence, sufentanil can exert greater analgesic effects over longer time compared with the same dose of fentanyl or morphine, and can lower the incidence of respiratory depression and adverse events ( Xu et al, 2020 ). Given the significant harm that opioid abuse poses to public health ( Volkow and McLellan, 2016 ), greater potency of sufentanil versus fentanyl and morphine may lead to accidental overdose of sufentanil ( Deeks, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through physical and mental nursing before and after the operation, the patients can have a deep understanding of the surgical process, the harm of emergence agitation, etc., so that the patients are in a relatively calm state for surgery. The observation and nursing of patients' status after general anesthesia, monitoring of patients' vital health status, timely feedback of patients' postoperative adverse reactions, and giving different degrees of psychological comfort to patients with emergence agitation can effectively reduce the threat to life and health [ 29 ]. To sum up, comfortable nursing could reduce the degree of pain of surgery, reduce the degree of agitation during postoperative recovery, and improve nursing satisfaction by adjusting the psychological state of patients during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%